Src controls castration recurrence of CWR22 prostate cancer xenografts. (11th October 2013) - Su, Bing; Gillard, Bryan; Gao, Lingqiu; Eng, Kevin H.; Gelman, Irwin H.
Abstract Recurrence of prostate cancer (CaP) after androgen‐deprivation therapy continues to have the greatest impact on patient survival. Castration‐recurrent (CR)‐CaP is likely driven by the activation of androgen receptor (AR) through multiple mechanisms including induction of AR coregulators, AR mutants or splice variants, and AR posttranslational modification such as phosphorylation by Src‐family and Ack1 tyrosine kinases. Here, we address whether Src is required for the CR growth of human CWR22 CaP xenografts. The shRNA‐mediated Src knockdown or treatment with the Src inhibitors, dasatinib or KXO1, reduced CaP recurrence over controls and increased time‐to‐recurrence following castration. Moreover, CR‐CaP [Src‐shRNA] tumors that recurred had similar Src protein and activation levels as those of parental cells, strengthening the notion that Src activity is required for progression to CR‐CaP. In contrast, the ability of dasatinib or KXO1 to inhibit Src kinase activity in vitro did not correlate with their ability to inhibit serum‐driven in vitro proliferation of CR and androgen‐dependent stable cell lines derived from CWR22 tumors (CWR22Rv1 and CWR22PC, respectively), suggesting that the in vitro proliferation of these CaP lines is Src independent. Taken together, these findings strongly suggest that Src is a potent and specific therapeutic target for CR‐CaP progression.